2017
DOI: 10.1128/mspheredirect.00272-17
|View full text |Cite
|
Sign up to set email alerts
|

Variable Virulence of Biotype 3 Vibrio vulnificus due to MARTX Toxin Effector Domain Composition

Abstract: Vibrio vulnificus is a serious infection linked to climate change. The virulence capacity of these bacteria can vary by gene exchange, resulting in new variants of the primary virulence toxin. In this study, we tested whether the emergence of an epidemic strain of V. vulnificus with a novel toxin variant correlated with a change in virulence. We found that restoring the biotype 3 toxin variant to the putative progenitor-type toxin resulted in dramatically increased virulence, revealing that the emergence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Notably, removal of the RRSP domain that cleaves Ras dramatically reduces virulence of V. vulnificus strain CMCP6, while removal of MCF did not dramatically affect virulence (Kwak et al, 2011;Gavin and Satchell, 2017). By contrast, completely swapping MCF and RRSP in place of ExoY and DmX in the BT3 V. vulnificus strain to match its putative progenitor strain dramatically increased virulence (Kim et al, 2017). Finally, a recent study found that the collection of certain effector domains could induce the expression of pro-inflammatory genes, while another strain with a different set of effectors can downregulate many pro-inflammatory genes (Murciano et al, 2017).…”
Section: Impact Of Effector Domain Composition On Virulencementioning
confidence: 98%
See 2 more Smart Citations
“…Notably, removal of the RRSP domain that cleaves Ras dramatically reduces virulence of V. vulnificus strain CMCP6, while removal of MCF did not dramatically affect virulence (Kwak et al, 2011;Gavin and Satchell, 2017). By contrast, completely swapping MCF and RRSP in place of ExoY and DmX in the BT3 V. vulnificus strain to match its putative progenitor strain dramatically increased virulence (Kim et al, 2017). Finally, a recent study found that the collection of certain effector domains could induce the expression of pro-inflammatory genes, while another strain with a different set of effectors can downregulate many pro-inflammatory genes (Murciano et al, 2017).…”
Section: Impact Of Effector Domain Composition On Virulencementioning
confidence: 98%
“…3). Indeed, effector 'crosstalk' may contribute to why bacterial strains with different effector combinations have differences in virulence (Kwak et al, 2011;Kim et al, 2017;Murciano et al, 2017). Effector crosstalk has already been directly demonstrated in the MARTX toxin of V. cholerae.…”
Section: Martx Toxin Effector Synergy and Crosstalk?mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, we have uploaded what we believe to be a great example of how the process should take place ( http://msphere.asm.org/sites/default/files/additional-assets/mSDSample.pdf ). We are grateful to Karla Satchell and her coauthors, as well as to Carmen Amaro and Jonathon Audia, the external solicited reviewers, for doing such a wonderful job and for graciously allowing us to post their documents relating to the Satchell laboratory’s report on Vibrio vulnificus virulence ( 2 ).…”
Section: Editorialmentioning
confidence: 99%
“…Although it is not its primary pathology, V vulnificus is capable of producing gastroenteritis among its clinical manifestations. This pathogen secretes a number of exotoxins and enzymes ( Liu et al, 2007 ), among which the cytolysin VvhA ( Kim et al, 2017 ) and metalloprotease Vvp ( Lee et al, 2008 ; Chen et al, 2017 ) are the most important join to RTX. This last toxin has been strongly associated with the virulence of this organism ( Lee et al, 2007 , 2008 ).…”
Section: Introductionmentioning
confidence: 99%